2002
DOI: 10.1046/j.1471-4159.2002.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activating factor‐induced apoptosis is inhibited by ectopic expression of the platelet activating factor G‐protein coupled receptor

Abstract: The pro-inflammatory lipid mediator platelet activating factor (PAF: 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) accumulates in ischemia, epilepsy, and human immunodeficiency virus-1-associated dementia and is implicated in neuronal loss. The present study was undertaken to establish a role for its G-protein coupled receptor in regulating neurotoxicity. PC12 cells do not express PAF receptor mRNA as demonstrated by northern analysis and RT-PCR. In the absence of the G-protein coupled receptor, PAF (0.1)1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
(87 reference statements)
0
31
0
Order By: Relevance
“…Abstract presented at the 67th Annual Meeting of the Society for Investigative Dermatology, May 3 to 6, 2006 Philadelphia, PA). Interestingly, however, Brewer and colleagues 39 have shown that PAF can have anti-and proapoptotic effects in cells, initiated by its G-protein-coupled receptor or occurring independently of this receptor. Furthermore, Southall and colleagues 40 have shown that the activation of the epidermal PAF receptor protected from apoptosis induced by either TNF-␣ or TNF-related apoptosis-inducing ligand and that this protective effect was inhibited by pretreatment with PAF receptor antagonists mediated by a nuclear factor-B-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Abstract presented at the 67th Annual Meeting of the Society for Investigative Dermatology, May 3 to 6, 2006 Philadelphia, PA). Interestingly, however, Brewer and colleagues 39 have shown that PAF can have anti-and proapoptotic effects in cells, initiated by its G-protein-coupled receptor or occurring independently of this receptor. Furthermore, Southall and colleagues 40 have shown that the activation of the epidermal PAF receptor protected from apoptosis induced by either TNF-␣ or TNF-related apoptosis-inducing ligand and that this protective effect was inhibited by pretreatment with PAF receptor antagonists mediated by a nuclear factor-B-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…3) PAFR-independent cell death can be inhibited by two PAF antagonists: the gingkolide BN 52021 and the fungal derivative Apoptotic PAF Signal Transduction in the Absence of PAFR-To provide mechanistic insight into how PAF transduces cell death in the absence of PAFR, we followed the internalization and metabolic fate of Bodipy fluorophore-conjugated PAF in PAF-sensitive cells (11,43). PC12 cells express all of the components of both cytosolic PAF-AH enzymes (I and II) but not plasma PAF-AH or PAFR.…”
Section: Cytosolic Paf-ahs Can Be Targeted Pharmacologically To Promomentioning
confidence: 99%
“…Although the majority of PAF effects are understood to be transduced by its G-protein-coupled receptor (PAFR) (10), PAFR signaling has been shown to be both pro-and anti-apoptotic. Ectopic PAFR expression exacerbates cell death induced by etoposide and mitomycin C but protects cells from tumor necrosis factor ␣, TRAIL, and extracellular PAF (6,7,11,12). These opposing effects likely depend upon the relative ratio of NF-B-dependent pro-and anti-apoptotic gene products elicited in different cell types in response to the combination of an external apoptotic inducer and PAF (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PC12-AC cells, a clonal derivate (Brewer et al, 2002) of the PC12 rat adrenal pheochromocytoma cell line (American Type Culture Collection), were maintained in complete media (RPMI 1640 containing 10% horse serum and 5% newborn calf serum) under normoglucose (11 mM) conditions. Cells were seeded in 96-well plates (1.25 × 10 4 cells/well) and allowed to adhere at 37…”
Section: Cell Culture Glucose Toxicity and Glucose Deprivation Condmentioning
confidence: 99%